Pentahelix's Strategy in Reducing the Risk of a COVID-19 Pandemic Disaster at Semaki Village, Umbulharjo Yogyakarta : Strategi Pentahelix Dalam Pengurangan Risiko Bencana Pandemi COVID-19 Kelurahan Semaki Kecamatan Umbulharjo, Yogyakarta - Haifani, Shodiq; Paripurno, Eko Teguh (Al-Hijrah Indonesia, 2022)
Pentahelix concept is an innovation in the field of disaster management which includes the government, academia, media, private sector and community. The pentahelix parties is needed stop the transmission of COVID-19. The Umbulharjo Kemantren contributed 45.45% of the number of confirmed COVID-19 patients in the City of Yogyakarta. Semaki has the lowest number of confirmed cases of COVID-19 compared to other Kelurahans in the Umbulharjo. This study aims to describe the role of the parties in reducing the impact, strategies of the parties in reducing the COVID-19 pandemic disaster in Semaki. This research is a field research to explain the COVID-19 disaster and the patterns used to deal with it. The data obtained from observations, document studies, questionnaires and interviews. Observations were made to observe objects and research subjects directly in the field, the results of the observations were recorded and used as material for interviews. Document studies are carried out by examining documents from the sub-district, incident records, and documents. The questionnaire was conducted by involving 100 respondents from the Semaki. Interviews were conducted with both formal and informal nature. The government make regulations and mobilize every element within the government according to the field of work, academics play a role in education and training on the use of online meetings, media does coverage, private sector contributes in food assistance and isolation places, and the community carried out spraying activities, provided assistance to isoman residents, collected data and carried out area monitoring.